2019
DOI: 10.26508/lsa.201800270
|View full text |Cite
|
Sign up to set email alerts
|

Human CST suppresses origin licensing and promotes AND-1/Ctf4 chromatin association

Abstract: Human CTC1-STN1-TEN1 (CST) is an RPA-like single-stranded DNA-binding protein that interacts with DNA polymerase α-primase (pol α) and functions in telomere replication. Previous studies suggest that CST also promotes replication restart after fork stalling. However, the precise role of CST in genome-wide replication remains unclear. In this study, we sought to understand whether CST alters origin licensing and activation. Replication origins are licensed by loading of the minichromosome maintenance 2–7 (MCM) … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(43 citation statements)
references
References 76 publications
(141 reference statements)
0
43
0
Order By: Relevance
“…Unlike yeast, mammalian CST is involved in several distinct DNA transactions in the cell, including telomere maintenance, replication rescue, dormant origin firing, origin licensing and DSB repair (23,(25)(26)(27)29,30,34). However, it has been difficult to identify the contribution of telomere versus non-telomere CST functions on genome stability and cell cycle progression.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Unlike yeast, mammalian CST is involved in several distinct DNA transactions in the cell, including telomere maintenance, replication rescue, dormant origin firing, origin licensing and DSB repair (23,(25)(26)(27)29,30,34). However, it has been difficult to identify the contribution of telomere versus non-telomere CST functions on genome stability and cell cycle progression.…”
Section: Discussionmentioning
confidence: 99%
“…In a similar manner, CST could stabilize TopBP1 by recruiting it to the chromatin. As to the mechanism of CST recruitment to stalled forks, we recently showed that CST interacts with the MCM2-7 helicase (25). Thus, CST could be recruited to stalled forks by MCM2-7 and then recruits TopBP1 to prevent degradation, stimulating ATR-mediated CHK1 phosphorylation.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations